2010
DOI: 10.1515/jaots-2010-0203
|View full text |Cite
|
Sign up to set email alerts
|

Design of In Situ Fenton Oxidation Based on the Integration of Experimental and Numerical Modelling

Abstract: Criteria for the design of In-Situ Fenton Oxidation (ISFO) is proposed and applied to the development of a pilot-scale treatment of a former refinery site contaminated by hydrocarbons. The proposed criteria takes in account both the regulatory and technical constraints that typically characterize the application of in situ remediation technologies. The proposed design strategy of the ISFO treatment is based on coupling experimental and numerical modelling of the ISFO treatment in an iterative way. Batch tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to Innocenti et al (2014), when increased volatilization was observed at a MTBE-contaminated groundwater site within the same timeframe as the one described here, 99% of the total reductions could still be attributed to chemical mineralization. The H 2 O 2 concentration then used (6%, 1.8 M) was close to the optimal for gas production as described by Baciocchi et al (2010). In the site treatment (Innocenti et al 2014) case, no additional catalysts were used but addition of peroxide was documented to have increased soil acidity from approximately pH 6 to pH 4, a level closer to the optimal pH range than the one described here.…”
Section: Discussionmentioning
confidence: 75%
“…According to Innocenti et al (2014), when increased volatilization was observed at a MTBE-contaminated groundwater site within the same timeframe as the one described here, 99% of the total reductions could still be attributed to chemical mineralization. The H 2 O 2 concentration then used (6%, 1.8 M) was close to the optimal for gas production as described by Baciocchi et al (2010). In the site treatment (Innocenti et al 2014) case, no additional catalysts were used but addition of peroxide was documented to have increased soil acidity from approximately pH 6 to pH 4, a level closer to the optimal pH range than the one described here.…”
Section: Discussionmentioning
confidence: 75%
“…When this oxidant comes into contact with inorganic compounds, such as iron oxyhydroxide and manganese oxyhydroxide catalysts, or with organic compounds commonly found in surface soils, it can quickly decompose, limiting the utility of ISCO for the remediation of contaminated sites. According to Baciocchi et al [48], these non-productive reactions may well lead to a loss of hydrogen peroxide above 50%.…”
Section: Scavengersmentioning
confidence: 99%